Intragenerational social mobility and depressive symptoms. Results from the French CONSTANCES cohort study - Hanno Hoven; Johannes Siegrist; Marcel Goldberg; Céline Ribet; Marie Zins; Morten Wahrendorf (Elsevier, 2019)
Background: To further explain the association between low socioeconomic position and increased risk of poor health, research started to consider life course conditions, including previous occupational positions and patterns of social mobility in the analysis. We describe patterns of intragenerational social mobility and investigate their associations with depressive symptoms. Methods: We use data from the French CONSTANCES study, a population-based cohort and restrict the sample to people aged 45 to 60. Based on detailed retrospective data with annual information on respondents' occupational position, we assess the modal social class for two time periods - early adulthood (age 25-34) and mid-adulthood (age 35-44). Depressive symptoms are measured by the Centre for Epidemiologic Studies Depression Scale (CES-D), using sex-specific cut-points. Results: Our study reveals that most respondents remained in stable working careers, but these careers were less frequent amongst participants with lower socioeconomic positions compared with higher ones. In contrast to several earlier findings we observe no independent associations of intragenerational social mobility processes and health once the social positions of origin and destination are considered. However, our findings confirm a social gradient in the prevalence of depressive symptoms for stable working careers. Conclusions: Our findings underline the importance of integrating data into analysis on starting and ending points of social mobility processes within entire histories of labor market participation. Keywords: Social mobility, Depressive symptoms, CONSTANCES cohort, Social class, Employment history